Evaluation of the durum wheat landrace genetic diversity using agro analysis and its benefit for human health - Ihsan, Mohammad; Khan, Arshad; Nazir, Nausheen; Nisar, Mohammad; Jan, Tour; Ullah, Shariat; Aziz, Tariq; Al-Asmari, Fahad; Alshareef, Sahar A.; Aljabri, Maha; Sameeh, Manal Y. (Italian Journal of Food Science, 2024)
Ancient wheat and landraces (traditional varieties) are fascinating to the consideration of scientists who are re-evaluating the healthy and dietary properties attributed to them by popular tradition. Wheat (Triticum durum) is one of the most significant crops that is grown all over the world. In the present study, 19 landraces were analyzed for genetic diversity through morphological and SDS-PAGE analysis. The highest coefficient of variance (18.91%) was found for spike length, and the lowest for days to maturity (1.51%). The genotype Malakand and Dolram produced a maximum number of seeds (42 and 46 seeds per plant), and the genotypes Dogai and Rasool Banda were found to be the tallest (73 and 71 cm, respectively). The genotype Kamar Kotki was found to mature early (165 days) while Doagi was found to mature late (171 days). Spike length was found to be positively correlated with plant height, leaf width, and leaf length. Leaf width was significant with spike length and the internode distance. The cluster analysis divided all the genotypes into six sub-clusters where the Asban and the Shekhan were placed at the extreme of the dendrogram. Based on the total seed storage proteins analysis, 18 (85.71%) bands were polymorphic while 14.28% bands were found to be monomorphic. Using Ward’s methods, all the genotypes were divided into two main lineages at 25% Euclidian distance and five sub-clusters at 75% distance. Our findings have significance for understanding the variations and relationships between various durum wheat genotypes and could serve as a basis for local elite durum germplasm that has been regionally adapted.